Juridical Analysis of the Ombudsman's Role in Healthcare Service Disputes - O.Munthe; P.Rangkuti (International Medical Journal Corp. Ltd, 2025)
Introduction: Healthcare public services are a fundamental right of citizens, yet maladministration often triggers complex disputes between patients and medical providers. While judicial routes exist, they are frequently prolonged, costly, and adversarial. This study examines the position and efficacy of the Ombudsman as an independent oversight institution in resolving healthcare service disputes. Methods: This research employs a normative juridical method, analyzing statutory provisions, legal doctrines, and administrative regulations related to public services and healthcare. Results: The findings reveal that the Ombudsman plays a pivotal role in mediating healthcare disputes arising from administrative misconduct, offering a non-adversarial mechanism that bridges the gap between rigid healthcare regulations and patient rights. However, its structural efficacy is often constrained by the non-binding nature of its recommendations. Discussion: The discussion integrates a comprehensive literature review regarding administrative law and medical law principles. It evaluates how the Ombudsman acts as an alternative dispute resolution forum, contrasting it with formal litigation, and analyzes the systemic barriers that prevent its structural interventions from achieving full enforcement. Conclusions: In conclusion, the Ombudsman serves as a crucial balancing force in healthcare disputes, but its institutional authority requires legislative strengthening. It is recommended that future legal reforms grant binding execution powers to Ombudsman recommendations to ensure absolute administrative accountability in the healthcare sector.